Effects of eccentric and concentric strength training on maximum strength, power variables and dynamic strength index - Rajalainen, Ville (2021)
Eccentric and concentric strength training have been studied and compared since 1890’s. Studies have reported mixing results regarding strength gains. Also, research focusing on the effects of these training modalities on variables of power output is scarce. Dynamic Strength Index (DSI) has been proposed to be an effective tool of assessing athlete’s strength qualities to direct future strength training optimally. DSI is described as peak force in dynamic movement divided by peak force in the subsequent isometric effort. Few studies have examined the effects of strength training on DSI, and no previous studies have compared the effects of concentric and eccentric strength training protocols. This study aimed to compare the effects of eccentric and concentric strength training on maximum strength, DSI, and maximal power output in untrained or recreationally trained adults. A total of 46 participants, including both men and women, completed the training intervention with maximal isolated isokinetic concentric or eccentric bench press exercises with a custom-made bench press device. Participants were divided in to concentric (CON, n=24, 30.0 ± 4.1 years, 1.73 ± 0.10 m, 72.0 ± 11.3 kg, 23.8 ± 2.7 BMI) and eccentric (ECC, n=22, 27.7 ± 5.2 years, 1.73 ± 0.07 m, 74.1 ± 10.5 kg, 24.7 ± 3.2 BMI) training groups with similar 1RM in dynamic bench press at baseline (p=0.94). Both groups trained twice per week for 10 weeks with PRE measurements at week 1, MID measurements at week 6, and POST measurements at week 10. 1RM test, isometric bench press, and bench press throw (BPT) with loads of 30%, 45%, and 60% of 1RM were performed at each testing session. Peak force in the isometric bench press and BPT were used to calculate DSI. No differences between the training methods were observed in 1RM, DSI, isometric bench press or BPT related variables. 1RM increased in both concentric and eccentric training groups from 57.6 ± 20.2kg to 59.3 ± 19.9kg and 56.7 ± 19.4kg to 61.1 ± 20.2kg PRE to MID, respectively (p<0.001). Both CON and ECC training groups increased their 1RM to 64.0 ± 21.3kg and 63.9 ± 19.9kg MID to POST, respectively (p<0.001). Peak force in isometric bench press increased from PRE to POST (p<0.05) and from MID to POST in both groups (ECC: 613.3 ± 190.4N to 659.1 ± 190.8N, p<0.001; CON: 599.0 ± 198.2N to 636.8 ± 209.9N, p<0.05). Peak force in BPT increased only in CON group with 60% 1RM load from PRE to POST (ECC: 153.7 ± 62.8 to 149.5 ± 60.7N; CON: 149.5 ± 59.3 to 171.0 ± 71.8N, p<0.05). Both groups increased their peak power from PRE to POST condition with all loads (30%1RM; ECC: 527.9 ± 178.4W to 548.4 ± 207.9W; CON: 490.1 ± 202.1W to 540.2 ± 178.4W, 45%1RM; ECC: 479.8 ± 190.7W to 552.5 ± 211.6W; CON: 447.5 ± 203.7W to 493.7 ± 179.3W; 60%1RM; ECC: 448.0 ± 164.7W to 497.8 ± 178.6W; CON: 412.3 ± 138.5W to 448.7 ± 143.3W). The present study showed that maximal isokinetic eccentric and concentric bench press strength training for 10 weeks induced similar changes in bench press 1RM, isometric peak force, and BPT performance. No changes in DSI were observed, although isometric peak force increased in both groups.